1993
DOI: 10.1902/jop.1993.64.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Retrieved Polytetrafluoroethylene Membranes: Morphological and Microbiological Observations

Abstract: Polytetrafluoroethylene membranes (ePTFE) used in guided tissue regeneration (GTR) are accessible to colonization by oral bacteria. The bacterial composition of the adherent biomass is unknown. We examined a total of 6 membranes that were retrieved after 4 to 6 weeks from human periodontitis sites, using optical and transmission electron microscopy (TEM) as well anaerobic cultivation. Five of the 6 membranes provided the microbiological data and microscopic data. TEM revealed an organized microbial mass coveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 14 publications
(1 reference statement)
2
48
1
2
Order By: Relevance
“…Premature exposure, especially of the e-PTFE membrane, allows for bacterial growth and eventual bacterial penetration of the membrane exposed to the oral cavity. Tempro and Nalbandian (1993) reported an organized bacterial mass, composed primarily of Streptococcus and Actinornyces spp. and Gram-negative facultative rods, on the e-PTFE membranes and suggested that bacterial colonization may affect connective tissue regeneration.…”
Section: (D) Gbr Used In Implantologymentioning
confidence: 99%
“…Premature exposure, especially of the e-PTFE membrane, allows for bacterial growth and eventual bacterial penetration of the membrane exposed to the oral cavity. Tempro and Nalbandian (1993) reported an organized bacterial mass, composed primarily of Streptococcus and Actinornyces spp. and Gram-negative facultative rods, on the e-PTFE membranes and suggested that bacterial colonization may affect connective tissue regeneration.…”
Section: (D) Gbr Used In Implantologymentioning
confidence: 99%
“…Therefore, titanium re-inforced non-degradable e-PTFE membranes are still favored by some clinicians. Early exposure of barrier membranes to the oral environment jeopardizes the outcome due to infection, mostly manifested around non-resorbable membranes, or due to rapid disintegration in case of resorbable membrane (De Sanctis et al, 1996;Mayrand & Grenier, 1985;Nowzari & Slots, 1995;Sela, et al, 2003;Simion, et al, 1994;Tempro & Nalbandian, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although ePTFE membranes remain stable throughout an extended period, their main limitation is the requirement for additional surgery for retrieval 8) . Furthermore, early spontaneous membrane exposure to the oral environment and subsequent bacterial colonization have been reported to be common phenomena associated with nonresorbable membranes, which frequently require early, premature retrieval 9) . Therefore, resorbable membranes with comparable clinical outcomes have become popular.…”
Section: Introductionmentioning
confidence: 99%